The Xanthomonas campestris pv. vesicatoria type III effector protein XopJ inhibits protein secretion: evidence for interference with cell wall-associated defense responses. - Bartetzko, Verena; Sonnewald, Sophia; Vogel, Florian; Hartner, Kristina; Stadler, Ruth; Hammes, Ulrich; Börnke, Frederik (Molecular Plant-Microbe Interactions, 2009)
The phytopathogenic bacterium Xanthomonas campestris pv. vesicatoria uses the type III secretion system (T3SS) to inject effector proteins into cells of its Solanaceous host plants. It is generally assumed that these effectors manipulate host pathways to favor bacterial replication and survival. However, the molecular mechanisms by which type III effectors suppress host defense responses are far from being understood. Based on sequence similarity, Xanthomonas outer protein J (XopJ) is a member of the YopJ/AvrRxv family of SUMO peptidases and acetyltranferases, although its biochemical activity has not yet been demonstrated. Confocal laser scanning microscopy revealed that green fluorescent protein (GFP) fusions of XopJ are targeted to the plasma membrane when expressed in plant cells, which most likely involves N-myristoylation. In contrast to a XopJ(C235A) mutant disrupted in the catalytic triad sequence, the wild-type effector GFP fusion protein was also localized in vesicle-like structures colocalizing together with a Golgi marker protein, suggesting an effect of XopJ on vesicle trafficking. To explore an effect of XopJ on protein secretion, we used a GFP-based secretion assay. When a secreted (sec)GFP marker was coexpressed with XopJ in leaves of Nicotiana benthamiana, GFP fluorescence was retained in reticulate structures. In contrast, in plant cells expressing secGFP alone or along with the XopJ(C235A) mutant, no GFP fluorescence accumulated within the cells. Moreover, coexpressing secGFP together with XopJ led to a reduced accumulation of secGFP within the apoplastic fluid of N. benthamiana leaves, further showing that XopJ affects protein secretion. Transgenic expression of XopJ in Arabidopsis suppressed callose deposition elicited by a T3SS-negative mutant of Pseudomonas syringae pv. tomato DC3000. A role of XopJ in the inhibition of cell wall-based defense responses is discussed.